Coating Medpor® Implant with Tissue-Engineered Elastic Cartilage - Dong Joon Lee (Journal of Functional Biomaterials, 2020)
Inert biomaterials used for auricular reconstruction, which is one of the most challenging and diverse tasks in craniofacial or head and neck surgery, often cause problems such as capsule formation, infection, and skin extrusion. To solve these problems, scaffold consisting of inert biomaterial, high-density polyethylene (Medpor®) encapsulated with neocartilage, biodegradable poly(DL-lactic-co-glycolic acid) (PLGA) was created using a tissue engineering strategy. PLGA scaffold without Medpor® was created to serve as the control. Scaffolds were vacuum-seeded with rabbit chondrocytes, freshly isolated from the ear by enzymatic digestion. Then, cell-seeded scaffolds were implanted subcutaneously in the dorsal pockets of nude mice. After 12 weeks, explants were analyzed by histological, biochemical, and mechanical evaluations. Although the PLGA group resulted in neocartilage formation, the PLGA–Medpor® group demonstrated improved outcome with the formation of well-surrounded cartilage around the implants with higher mechanical strength than the PLGA group, indicating that Medpor® has an influence on the structural strength of engineered cartilage. The presence of collagen and elastin fibers was evident in the histological section in both groups. These results demonstrated a novel method of coating implant material with engineered cartilage to overcome the limitations of using biodegradable scaffold in cartilage tissue regeneration. By utilizing the patient’s own chondrocytes, our proposed method may broaden the choice of implant materials while minimizing side effects and immune reaction for the future medical application.